Ekphrasis The Illusion of the Natural Sign - Krieger, Murray (Johns Hopkins University Press, 2019)
Originally published in 1992. What, in apparently pictorial poetry, do words represent? Conversely, how can words in a poem be picturable? Murray Krieger develops a systematic theoretical statement out of answers to such questions. Ekphrasis is his account of the continuing debates over meaning in language from Plato to the present. Krieger sees the modernist position as the logical outcome of these debates but argues that more recent theories radically question the political and aesthetic assumptions of the modernists and the two-thousand-year tradition they claim to culminate. Krieger focuses on ekphrasis-the literary representation of visual art, real or imaginary-a form at least as old as its most famous example, the shield of Achilles verbally invented in the Iliad. He argues that the "ekphrastic principle" has remained enduringly problematic in that it reflects the resistant paradoxes of representation in words. As he examines the conflict between the spatial and temporal, between vision-centered and word-centered metaphors, Krieger reveals how literary theory has been shaped by the attempts and the deceptive failures of language to do the job of the "natural sign."